A rede telegráfica em Goiás: origem, controle e sentido territorial - Denis Castilho; Roberto Gonçalves Pacheco; Marcelo Barbosa Barreto (Confins)
Telegraph was installed in the state of Goiás (Brazil) in 1890. The expansion of this technical network in the territory of Goiás was marked by two main spatialities. The first has as focus military strategies, exclusive use and control of the territory; and the second, the more general demands of communication and multiple uses. Until 1913, telegraph wires were deployed independently of other networks. Subsequently, they followed the layout of the tracks, adding services and expanding the communication system of the locations served by the railway network. This study analyzes the origin and the territorial direction of the telegraph in Goiás by the end of the 19th and beginning of the 20th century. The methodological procedures were based on bibliographic research, data and information in newspapers published between 1894 and 1914, in Brazilian official reports of the Empire and the Republic (1860, 1891 and 1899), analysis of decrees information and obtaining data through the collection of historical letters from the National Archives. The results reveal the pioneering role of the telegraph in the communication system between the coast and the hinterland, showing its strategic role in defining borders, in economic-military interests, in regional exchanges, and show how this network was constituted as a key instrument for the construction of a new sense of communication, control and power.